Comparative study and storage stability of hepatobiliary enzymes in ruminants and dogs of humid -- tropics - Divya P.D (Department of Vetetinary Biochemistry, College of Veterinary and Animal Sciences, 2009)
The present research was designed and conducted with the objectives of assessing the normal serum activity of hepatobiliary enzymes such as, ALT, AST, ALP and GGT for different animal species reared under the hot humid climatic conditions and to identify the ideal storage condition for each enzyme in these species by keeping sera samples at room temperature, 4 ºC and -20 ºC up to 14 days. The study was performed in adult healthy female crossbred cattle, Murrah buffalo and crossbred goats maintained at University Livestock Farms, College of Veterinary and Animal sciences, Mannuthy and dogs of mixed breeds maintained at nearby kennels during the period of April to October 2008.